2012
DOI: 10.1364/josab.29.000538
|View full text |Cite
|
Sign up to set email alerts
|

Localized defect modes in dual-periodical multilayer structures based on porous silicon

Abstract: We present an experimental study of the resonance modes in dual-periodical multilayer structures based on porous silicon. These multilayered structures are composed by stacking N times two substructures A, and B, i.e., A n B m N . The A n and B m are in turn composed of two different period units, a and b, respectively, where subscripts n and m are the period number in the a and b substructures. Both substructures a and b consist of a pair of alternating layers with high and low refractive indices n 1 and n 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The decreasing or the increasing number of layers of the substructure, acting as a defect in the system (substructure B for the samples considered here), results in the widening or narrowing of the peaks and consequently, the value of FWHM [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The decreasing or the increasing number of layers of the substructure, acting as a defect in the system (substructure B for the samples considered here), results in the widening or narrowing of the peaks and consequently, the value of FWHM [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Pérez et al [34] reported DP structures from PSi multilayers. Dual-periodic structure (Figure 1) is composed of two substructures, A and B , repeating alternatively in the sequence AnBmAnBm...AnBm=(AnBm)N.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations